Leaf cellulose density as the key determinant of inter- and intra-specific variation in leaf fracture toughness in a species-rich tropical forest - Kitajima, Kaoru (Interface Focus, 2016)
Leaves as the main photosynthetic organ of plants must be well protected against various hazards to achieve their optimal lifespans. Yet, within-species variation and the material basis of leaf strength have been explored for very few species. Here, we present a large dataset of leaf fracture toughness from a species-rich humid tropical forest on Barro Colorado Island, Panama, reporting both among- and within-species variation in relation to light environment (sun-lit canopy versus shaded understorey) and ontogeny (seedlings versus adults). In this dataset encompassing 281 free-standing woody species and 428 species-light combinations, lamina fracture toughness varied ca 10 times. A central objective of our study was to identify generalizable patterns in the structural and material basis for interspecific variation in leaf lamina fracture toughness. The leaf lamina is a heterogeneous structure in which strong materials in cell walls, such as cellulose and lignin, contribute disproportionately to fracture toughness. We found significant increases in leaf fracture toughness from shade to sun and from seedling leaves to adult leaves. Both within and across species, leaf fracture toughness increased with total bulk density (dry biomass per unit volume) and cellulose mass concentration, but decreased with mass concentrations of lignin and hemicelluose. These bivariate relationships shift between light environments, but leaf cellulose density (cellulose mass per unit leaf volume) exhibits a common relationship with lamina fracture toughness between light environments and through ontogeny. Hence, leaf cellulose density is probably a universal predictor of leaf fracture toughness.